Molecular characterization of a farmer-preferred maize landrace population from a multiple-stress-prone subtropical lowland environment - Fortunate Makore; Edmore Gasura; Caleb Souta; Upenyu Mazarura; John Derera; Meluleki Zikhali; Casper Kamutando; Cosmos Magorokosho; Shorai Dari (Society for Indonesian Biodiversity, 2021)
Abstract. Makore F, Gasura E, Souta C, Mazamura U, Derera J, Zikhali M, Kamutando CN, Magorokosho C, Dari S. 2021. Molecular characterization of a farmer-preferred maize landrace population from a multiple-stress-prone subtropical lowland environment. Biodiversitas 22: 769-777.  The study was conducted to assess genetic diversity of 372 maize lines using 116 single nucleotide polymorphism (SNP) markers. Three hundred and forty-seven lines were S1 lines (coded J lines) from a local maize landrace population and twenty-five were the widely used standard lines. The number of alleles per marker ranged from two to four and the average was three alleles.  The average polymorphic information content (PIC) value of 0.405 indicates high genetic diversity for maize lines evaluated in this study. Population structure revealed three distinct sub-populations. Sub-population 1 contained two J lines; sub-population 2 contained five J lines and sub-population 3 contained the rest of the J lines and all the standard lines. Analysis of molecular variance (AMOVA) identified 22% variance among and 78% variance within the three subpopulations, indicating high gene exchange and low genetic differentiation. Hierarchical cluster analysis further divided the lines into nine subgroups placing some of the J lines into known heterotic groups', i.e.,  J30_3, J393_4, J393_3, and J393_1 in CIMMYT heterotic group B. Allelic variation observed can be a source of allele combination for breeding programs interested in widening their genetic base. The private alleles that were present in the J lines suggest availability of stress-tolerant genes that breeders can incorporate in new hybrids.